Exogenous L-carnitine Administration Ameliorates the Adverse Effects of Heat Stress on Testicular Hemodynamics, Echotexture, and Total Antioxidant Capacity in Rams - El-Sherbiny, Hossam R.; El-Shalofy, Amr S.; Samir, Haney (Frontiers in Veterinary Science, 2022)
Heat stress (HS) diminishes the testicular antioxidant defense systems, which adversely affect the testicular blood perfusion. Improving the testicular hemodynamics during HS conditions is of a great impact on the whole reproductive performance in rams. The current work aimed to evaluate the ameliorative effects of L-carnitine (LC) on the testicular blood flow and echotextures as well as on the total antioxidants (TAC) and nitric oxide (NO) concentrations in the serum during HS conditions in rams. Testicular blood flow was evaluated through scanning of the supra-testicular artery (STA) spectral patterns through pulsed Doppler ultrasonography [peak systolic velocity (PI), end-diastolic velocity (EDV), time average maximum velocity (TAMAX), resistive index (RI), and pulsatility index (PI)], while the echotexture assessment of testicular parenchyma was performed by a computerized software program. Moreover, TAC and NO concentrations were assayed colorimetrically using the spectrophotometer. There were significant decreases (P < 0.05) in values of PSV at 48 and 168 h (23.45±0.39 cm/s, 23.37±1.41 cm/s, respectively), and TAMAX at 1, 48, and 168 h (17.65±0.95 cm/s, 17.5±0.13 cm/s, 16.9±1.05 cm/s, respectively) after LC administration compared to just before administration (31.92±1.13 cm/s, 21.58±0.92 cm/s, respectively). Values of RI and PI of the examined STA significantly decreased, especially at 1 h for RI (0.45±0.02), and 1 and 48 h for PI (0.66±0.06, 0.65±0.05, respectively) after LC treatment to 0 h (0.55±0.03, 0.84±0.06, respectively). Whereas the EDV values didn’t show any significant (P < 0.05) changes in all the experimental time points. There were significant (P < 0.05) increases in the values of pixel intensity of the testicular parenchyma, especially at 1 and 168 h (78.71±2.50, 88.56±4.10, respectively) after LC administration, compared to just before administration (69.40±4.75). Serum NO levels tend to increase after administration LC administration (P = 0.07) concerning just before administration. While TAC values showed significant gradual increases and reached the highest values at 168 h (2.75±0.58 mM/L) after LC administration, compared to 0 h (1.12±0.05 mM/L). In conclusion, exogenous L-carnitine administration ameliorates testicular hemodynamic disruptions, as measured by spectral Doppler ultrasonography, via augmentation of the rams’ total antioxidant capacity under heat stress conditions.